Beyond Just Ballots - MARYUM LUBNA (Graduate School of International Studies Ajou University, 2024)
Youth Political Activism pertaining to the changing political participatory behavior of the youth and its significance in cultivating liberal democratic values in the society is an underexplored subject, especially in the Global South’s context. Therefore, this thesis tries to research the barriers faced by the Pakistani youth in their political activism and participation. The research attempts to understand the nature of the problems and how they have changed over time due to the change in the traditional forms of political participation catalyzed by Digital Social Networks. The thesis further explores the relationship between youth political activism in cultivating liberal democratic values. The researcher put forwards two research questions 1. What are the barriers to the active participation of Pakistani youth in the political spheres? 2. How can youth’s political activism create an environment conducive to fostering democratic values and in sustaining a consistent democracy? To achieve this the researcher used a mixed method research design and the research relied mostly on non-numerical data i.e. qualitative methods with a field survey and a semi-structured interview. The survey data was analyzed through google forms and excel whereas interview data was analyzed through manual coding. The result from the data shows no change in the nature of the barriers faced by the youth of today, as challenges that existed decades ago still exists. But the research did show changes in the political participatory behavior of the youth due to information implosion and this implosion seems to be responsible for the cognitive shift among the youth of Pakistan. But Pakistani politics remains far from the activism based and cause oriented politics, significant for the cultivation of liberal democratic values from the grass root level. Future research on this issue can focus on the religious aspects of the issue in depth and investigate how it impacts youth’s political participatory behavior in a country like Pakistan. Keywords: Political activism, Political Participation, Political Socialization, Digital Activism, Social Movements, Civic Engagement, Youth, Democracy,Pakistan.
학위논문(석사)--국제개발협력과,2024. 8
Keywords: Civic Engagement; Pakistan; Politics; Youth Political Activism